Rancang Sistem Informasi Akuntansi Siklus Pendapatan Hotel “X” di Surabaya - Evando Callestyo; Priskila Adiasih (Business Accounting Review, 2017)
The research aimed to see the effectiveness of the revenue cycle of accounting information system in hotel. The study case that be used will showed that cash control was very important to hotel because cash management of a hotel is a hotel asset that very easily to be stolen. The system was created not only just to separate the jobs and obligations of employees but also to process the data to become information that helped leader to do internal control.            The result of research about accounting information system in “X” hotel showed the importance of integrated accounting information system to reach the growth of the company. The information system that saved well and connected by computerazation produced accurate revenue information and help the company to take fast decision.